Efektivitas Gerakan Sosial Berbasis Twitter Dalam Kasus Penyerangan Palestina 2023 - Meiliani, Adinda; Dewi, Putri Ayu Zahra; Urfa, Wardah Destia (Indonesian Democracy Research Center, 2024)
The Palestine–Israel conflict escalated again in October 2023 when Hamas launched an attack on Israel, triggering a massive military response. This situation resulted in thousands of casualties, predominantly among Palestinians, and sparked a wave of global solidarity through social media, particularly Twitter. This study aims to analyze the effectiveness of Twitter in facilitating digital social movements related to the 2023 Palestine–Israel conflict, focusing on the use of hashtags #FreePalestine, #CeasefireNow, and #BoycottIsraeliProducts. Employing a qualitative case study and document analysis, the research examines Twitter’s role in raising public awareness, mobilizing transnational solidarity, and encouraging concrete actions beyond the digital sphere. The findings reveal that Twitter plays a crucial role not only as a channel of communication but also as a strategic space that connects online activism with offline actions, such as demonstrations, boycott campaigns, and fundraising. An analysis using Media Dependency Theory and the concept of Hashtag Activism underscores that social media can strengthen collective empathy, shape global public opinion, and serve as an effective instrument in the struggle for humanitarian justice.